Effects of Interaction between New Rice Varieties and Plant Spacing to Productivity of Rice - -, Ikhwani - (Informatika Pertanian, 2015)
The most effective method to increase rice productivity in one location is to adapt the best combination between the high yielding rice variety and the optimum plant spacing. The objectives of this experiment to observe plant growth characteristic of each high yielding rice variety under each plant spacing to increase rice productivity. Field experiment was conducted at Toroh Regency, Grobogan District, Central Java during 2014 dry season. Treatments were arranged according to a split plot design, with three replications. The main plots (Plant spacings), namely T1- Equal spacing/Tegel 25 cm x 25 cm; T2- Legowo 2:1 (25---50) cm x 12,5 cm; T3- legowo 4:1 empty (25 – 50) cm x 12,5 cm dan T4- legowo 4:1 full (25 – 50) cm x 12,5 cm. The sub plots (variety): Ciherang, Inpari 10, Inpari 15 and Inpari 16.The yields of the rice varieties in this experiment are highly significantly different. It was found one introduced variety produced higher yield than Ciherang, namely Inpari 16 (5.93 + 0.43 ton 14% dry grain/ha). The two other introduced varieties (Inpari 10 and Inpari 15), produced 5.03 + 0.19 and 5.00 + 0.22 ton 14% dry grain/ha, the same or slightly lower than Ciherang. The highest yield occurred when Inpari 16 planted using Legowo 4 : 1 empty, namely 6.57 ton 14% dry grain/ha, consistently produces higher yield than the other varieties do at each plant spacing treatment. Rice yields of Ciherang were relatively more stable under different plant spacings compared with the other varieties. Inpari 10 at harvest stage having 19 tillers per hill under equal spacing 25 cm x 25 cm, decreased to 12 tillers per hill under Legowo 4 : 1 full. Ciherang with the medium size of grains have 1000 grain weight of 23.9 gram, and Inpari 10 25.3 gram. Based on the results of this experiment it is concluded that Inpari 16 planted under Jajar Legowo 4 : 1 empty (25 – 50) cm x 12.5 cm is the best. However, it is suggested to be evaluated acceptability by the local farmers.